Strengthening Distinctiveness of Law Study Programs: A SWOT-Based Analysis in South Sulawesi - Firmansyah, Firmansyah; Sabaruddin, Sabaruddin; Kulle , Haris; Hardianto, Hardianto; Syahrir , Syahdi; Abidin , Furqan Mulkia (Universitas Muhammadiyah Makassar, 2025)
The urgency of this research arises from intensifying competition among law faculties and study programs in South Sulawesi, which demands a clear strategic positioning and distinctive profile for each program. This study aims to analyze the distinctiveness of law study programs in several universities in South Sulawesi by employing a Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach to identify internal and external factors influencing their competitiveness and differentiation. Using a qualitative descriptive design, data were collected through observation, in-depth interviews with key stakeholders, and an extensive review of institutional and policy documents. The findings indicate that program differentiation can be systematically developed through market needs analysis and benchmarking, the formulation of visions and missions grounded in institutional core values, and curriculum development aligned with each university’s core business and regional characteristics. The strengths of the examined law programs include lecturer competence, relatively adaptive curricula, and networking with local legal and governmental stakeholders, while weaknesses are evident in limited facilities, constrained research resources, and insufficiently structured internship schemes. Opportunities are created by the high demand for qualified legal professionals and the dynamic evolution of national regulations, whereas major threats stem from intense inter-program competition and shifting higher education policies. The novelty of this study lies in its SWOT-based comparative mapping of multiple law study programs within a single geographic region, simultaneously identifying their substantive differentiation. The research contributes strategic recommendations for enhancing program competitiveness by strengthening flagship academic offerings, expanding collaboration with legal institutions, and optimizing internal resources to improve academic quality and competitive positioning at regional and national levels.